HUBUNGAN ANTARA KEPUASAN KERJA DENGAN KOMITMEN AFEKTIF PADA KARYAWAN - Puti Amallia; A.J. Tjahjoanggoro; Setiasih Setiasih (CALYPTRA, 2020)
Affective commitment is a situation where a person feels comfortable and happy working in their organization, in addition they also feel themselves identified as a member or part of their company. In affective commitment, there are several factors that can influence the emergence of these commitments, such as job satisfaction (Mowday et al., 1982). Employees who receive satisfaction from their workplace, they will show a pleasant attitude towards the job and will eventually lead to a committed attitude to the organization where they work. This study aims to examine the relationship between job satisfaction with affective commitment owned by employees of PT. PJB Services. The method used in this study is a quantitative survey. Subjects in this study were 117 permanent employees at PT. PJB Services. The results of statistical tests with Pearson's Correlation technique showed a relationship between job satisfaction and affective commitment (r = 0.699; sig: 0.000).